Free of charge - Zars, Pär (2009)
This thesis examines the value of Swedish forests as carbon sink in the perspective of increases in greenhouse gas concentration in the atmosphere, sometimes referred to as "global warming". This environmental problem would be even worse if our ecosystems did not absorb large amounts of carbon dioxide (CO2), taking it away from the atmosphere for a longer or shorter time. The forests in Sweden are a sink for CO2 from the atmosphere. This thesis tries to estimate the value of this service that is provided for free; it combines forecasts for the sink with cost for reducing CO2 emissions and derives a value of the service. The estimated value of a carbon sink of 15 Mt/year range from 2.6 to 7.1 billions/year, depending on the assumptions made. The value of a 2 Mt sink/year could vary from 0.54 to 1.7 billions/year. The main factors that influence the value of the sink are: the size of the sink, the national emission target, the forecasted emissions, the shape of the cost curves, whether trading with emission permits is allowed and if trade is allowed, the market price of permits.